Leveraging an empire : settler colonialism and the legalities of citizenship in the Pacific Northwest - Tyler, Jacki Hedlund (Lincoln [Nebraska] : University of Nebraska Press, 2021)
Leveraging an Empire examines the process of settler colonialism in the developing region of Oregon through an evaluation of Oregon's exclusionary laws between the years 1841 and 1859.
Introduction: A colonial outpost -- Oregon and the making of a settler colony in the Pacific Northwest -- The dispossession of American Indians and the right to exist -- Understanding immigration restrictions through arguments of slavery and labor -- Incorporated definitions of land ownership -- The privileged right to an education -- Implications of citizenship in suffrage and naturalization laws -- Conclusion: Defiant subjects and their legacies.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed July 6, 2021).
JSTOR
Keywords: Citizenship -- Oregon Territory -- History; Citizenship -- Northwest, Pacific -- History; HISTORY -- United States -- State & Local -- Pacific Northwest (OR, Wash.); Citizenship; United States -- Oregon Territory; Pacific Northwest; History